Supratherapeutic utilization of paracetamol versus ibuprofen among <12-year-old children in primary care in Istanbul - AKICI, AHMET (My University, 2023)
Background Paracetamol and ibuprofen are the most preferred analgesics for pain and fever management in children. Prescribing of these drugs in supratherapeutic doses may predispose to their toxicity. We aimed to compare prescribing patterns and potential overdosing of paracetamol and ibuprofen in primary care for Methods We analysed paracetamol- and ibuprofen-containing prescriptions (PCPs, n = 173,575 and ICPs, n = 145,655) of 1- to 11-year-old children, issued by 3:1 systematically sampled primary care physicians (n = 1,431) in Istanbul during 2016. We compared drug use parameters and prescriptions surpassing daily and single-use dose limits for paracetamol and ibuprofen. Results We identified that 29.9% of PCPs and 20.8% of ICPs were generated for those aged 1-2 years. Concomitant analgesic use was higher in ICPs than in PCPs (15.1% vs. 12.8%). We found that 4.4% of PCPs and 3.1% of ICPs exceeded maximum daily dose limit of paracetamol and ibuprofen, respectively (P < 0.001). This was more common in girls (5.1% and 3.3%, respectively) and at 1 year of age in both groups (9.2% and 8.5%, respectively). Single-use supratherapeutic dosing was encountered in 16.5% of PCPs and 13.2% of ICPs (P < 0.001, pessimistic model) and in 8.6% of PCPs and 10.6% of ICPs (P < 0.001, optimistic model). Conclusions Paracetamol and ibuprofen were generally used in primary care for similar clinical conditions with subtle differences. However, more pronounced in younger children and girls, potential overdosing seems to be more practiced for paracetamol than ibuprofen both in terms of maximal daily and single-use setting.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; BİRİNCİL SAĞLIK BAKIMI; Klinik Tıp; Klinik Tıp (MED); TIP, GENEL & DAHİLİ; PRIMARY HEALTH CARE; CLINICAL MEDICINE; Clinical Medicine (MED); MEDICINE, GENERAL & INTERNAL; Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; ibuprofen; overdose; paediatrics; paracetamol; preadolescence; supratherapeutic; DOSING ERRORS; ACETAMINOPHEN; MEDICATION; ANALGESICS; OVERDOSE; SAFETY